Videofashion specials. - Cardin, Marlene McGinnis; Charney, Nicolas H. (Fashion studies online: the videofashion library, 2013)
"Videofashion Specials is swim-sational with more action from Miami S/S 2013. Monica Wise presents three unique collections--L*SPACE, The Collection, and MAIO Swim--to satisfy her diverse clientele. At ANK, Mirla Sabino makes her first Miami Swim appearance since moving back to Brazil. DORIT debuts a plethora of prints and modern cuts for S/S 2013, Poko Pano brings South American flavor to South Beach, and Mara Hoffman's hippie traveler is well-suited for summer."--Publisher website.